POTENSI HASIL PERIKANAN TANGKAP DAN SUMBER DAYA LINGKUNGAN DI WILAYAH PESISIR UNTUK PENGEMBANGAN DESTINASI PARIWISATA DI PACITAN, JAWA TIMUR - Putranto, Anggoro; Nurfaiza, Ulfi; Mulabbi, Andrew; Jani, Jani (Social Landscape Journal, 2025)
Indonesia, as an archipelagic nation with an extensive coastline, influences the resource potential in coastal regions, including fisheries, the fishing industry, ports, and tourism. This potential renders coastal regions a dynamic interface between land and sea. Coastal communities should consistently endorse the available potential due to their expertise, competencies, and community advancement. The improper use of natural resources and the coastal environment can lead to numerous issues and result in the depletion of potential resources. Community development in the management of coastal and marine resources can be enhanced to support tourism activities, including the provision of local souvenirs and tourist services. This study aimed to assess the potential of capture fisheries and coastal environmental resources to facilitate the development of new tourist destinations in Pacitan Regency. The qualitative research employed methods of field observation and documentation. The findings indicated that capture fisheries in 2023 generally experienced an increase, whereas the decline was attributed to climatic conditions in the southern sea, which occasionally prevented fishermen from venturing out to sea. Fisheries serve not only community requirements but also facilitate fish processing to enhance tourism activities, transforming fish into souvenirs for coastal tourism. The construction of the JLS road facilitates the development of coastal tourism destinations, although certain areas remain challenging to access from the main road. Surfing sports tourism is a prominent destination, predominantly attracting international tourists. A classification of hugging beaches offers developmental prospects for ports and diverse marine tourism in Pacitan Regency.